2007
DOI: 10.1038/oby.2007.320
|View full text |Cite
|
Sign up to set email alerts
|

Basal Metabolic Rate and Autonomic Nervous System Dysfunction in Men With Spinal Cord Injury

Abstract: YILMAZ, BILGE, EVREN YASAR, SALIM GOKTEPE, RIDVAN ALACA, KAMIL YAZICIOGLU, UGUR DAL, AND HAYDAR MOHUR. Basal metabolic rate and autonomic nervous system dysfunction in men with spinal cord injury. Obesity. 2007;15:2683-2687. Objectives: The purpose of this study was to determine the relationship between autonomic nervous system dysfunction and basal metabolic rate (BMR), and the effect of spasticity on basal metabolic rate. Research Method and Procedures: Twenty men (11 paraplegic and 9 tetraplegic) with Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…If studies by the same authors were identified and found to include similar participants and mean REE values (n = 4), [11][12][13][14] the study with the largest sample size was included. Case studies were excluded because of the low level IV evidence, 15 and studies with adolescent data were excluded as the review was confined to the adult population only.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…If studies by the same authors were identified and found to include similar participants and mean REE values (n = 4), [11][12][13][14] the study with the largest sample size was included. Case studies were excluded because of the low level IV evidence, 15 and studies with adolescent data were excluded as the review was confined to the adult population only.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…For example, Buchholz et al 4 reported in 17 men with SCI, a BMR of 6499 kJ/day. BMR reported for 20 individuals with SCI by Yilmaz et al 33 was 6082 kJ/day.…”
mentioning
confidence: 99%
“…It seems that both groups have lower BMR and RMR values. Moreover, the group with spinal cord injuries showed lower FFM and reduced sympathetic nervous system activity in some studies [21,32]; however, in another study [2], these values were not actually lower. Muscle atrophy in poliomyelitis patients may not be caused by chronic wheelchair use but by the disease itself.…”
Section: Discussionmentioning
confidence: 96%
“…Seventeen articles were excluded from the systematic review after the full reading. Ten of these did not compare the disabled subjects to able-bodies subjects [2,4,11,12,13,14,15,16,17,18], 2 were review articles [7,19], 1 presented data from a nonadult population [20], 1 examined tetraplegia only [21], 2 were influenced by acute effects [22,23] and 1 evaluated the cost of ambulation only [24]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation